Ethical Education in the Perspective of Imam Az-Zarnuji - Suwanto, Suwanto; Lubis, Anisah Sari; Hanum, Azizah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
This study explores the views of Imam Az-Zarnuji on ethical education, as outlined in his classical work, "Ta'lim al-Muta'allim". The research highlights the importance of ethical education in the development of individual character and morality from an Islamic perspective. Through textual analysis, this study identifies the ethical principles taught by Imam Az-Zarnuji, such as sincere intentions, respect for teachers, the importance of beneficial knowledge, and the continuous effort in seeking knowledge. The study also discusses the relevance of these teachings in the context of modern education, demonstrating how traditional principles can be applied to address current moral and ethical challenges. The findings of this research aim to enrich the understanding of ethical education and offer practical guidance for educators and learners in the endeavor to cultivate noble character in accordance with Islamic teachings.